Use of Stream of Consciousness in Brick Lane: A Psychoanalytical Approach to Study Nazneen’s Evolution - Jabin Haque, Manfath (International Journal of Scientific Research and Management (IJSRM), 2022)
This paper attempts an interpretive study of Monica Ali’s use of steam of consciousness in her first novel Brick Lane (2003), examining the psychological connection with this technique to comprehend the protagonist Nazneen’s evolutionary expedition. Brick Lane starts with the stillbirth of Nazneen and by her mother’s influence she learns to accept fate without any question. After her marriage with Chanu, she becomes a British immigrant and embarks her journey to adjust in a new place, new life and to form a new identity beyond the patriarchal constraints. Throughout the novel, she undergoes various internal and external dilemma and troubles; but, she establishes her own identity by attaining economic emancipation and by establishing her logical opinion. This paper purports to interpret step by step journey of ‘a village girl’ Nazneen towards her transformation as an independent woman retaining her native cultural values. The study identifies the stream of consciousness used by the author to reveal the mind’s workings of Nazneen behind her behaviours and activities. This article attempts to explore the psychological interpretation of Nazneen’s thoughts and actions. In this regard, Freud’s theory of ‘unconscious’ and ‘conscious’ mind is used to explore how her stream of consciousness works for the readers to dive deep into the character to comprehend her predicament and upswing.  This paper presents, through a psychoanalytical approach, an in-depth textual interpretation of Nazneen’s story with a specific reference to her stream of consciousness.